Geography, Trade and Growth: Problems and Possibilities for the New Zealand Economy - Philip McCann (New Zealand Government, The Treasury, 2003)
This paper discusses the latest thinking in the relationships between the economics of trade, geography and industrial clusters. The aim of the paper is to explain the relevance of these various arguments for the economy of New Zealand and to suggest a possible public policy role for overcoming the growth problems associated with geographic periphery. As we will see, much of the current thinking on the relationships between geography, trade and clusters implies that New Zealand's long-term growth prospects are rather weak. However, it will be argued here that a detailed consideration of these relationships, plus some evidence from the UK, also provides some guidance as to possible strategies which New Zealand can employ to promote growth. In particular, the development of public policies which are specifically aimed at reducing the spatial market-area constraints of the New Zealand small-firm sector may be worthwhile.
Keywords: R11; F12; L14; 330; trade; geography; clusters; exports; public policy